2014
DOI: 10.1002/app.40710
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric coaxial filaments produced by coextrusion of poly(vinylidene fluoride) and electrically conductive inner and outer layers

Abstract: The development of new thermoplastic polymer-based piezoelectric sensors with filament geometry is described. These filaments are appropriate for integration into textiles and provide new possibilities in the design and development of low-cost flexible sensors produced at high rates. The developed three-layered piezoelectric monofilaments have been produced by coextrusion using poly(vinylidene fluoride) and two different polypropylene-based electrically conductive polymers. Filaments with about 800-mm diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Coaxial filament based piezoelectric sensors with piezoactive polymers, e.g. P(VDF-TrFE) and PVDF, with copper filament with thin layer of conductive materials and conductive inner and outer layers have achieved pressure sensitivity of 30-380 mv to applied pressure of 0-2 kPa and piezoelectric coefficient d1r 2.78-3.59 pC/N measured through charge amplifier, respectively [14][15]. Other types of printed structures, such as PVDF-tourmaline [16] have achieved sensitivities of 1.72-2.06 V with impact test of falling object of 1.02 kg at height of 0.05 m, that equals to 6.7 kPa pressure.…”
Section: Piezoelectric Coefficients (D33)mentioning
confidence: 99%
See 2 more Smart Citations
“…Coaxial filament based piezoelectric sensors with piezoactive polymers, e.g. P(VDF-TrFE) and PVDF, with copper filament with thin layer of conductive materials and conductive inner and outer layers have achieved pressure sensitivity of 30-380 mv to applied pressure of 0-2 kPa and piezoelectric coefficient d1r 2.78-3.59 pC/N measured through charge amplifier, respectively [14][15]. Other types of printed structures, such as PVDF-tourmaline [16] have achieved sensitivities of 1.72-2.06 V with impact test of falling object of 1.02 kg at height of 0.05 m, that equals to 6.7 kPa pressure.…”
Section: Piezoelectric Coefficients (D33)mentioning
confidence: 99%
“…In addition, the other type of filaments reported mostly utilize piezo-active PVDF-blends or ABS that have relative low melting temperature of ≤ 180 C [14][15][16][17]23]. Thus, making them unsuitable for high temperature sensor applications above 200 C. The depoling and Curie temperatures of such materials are even lower (roughly 100 C), thus the applicability for sensing at elevated temperatures is even more limited.…”
Section: Piezoelectric Coefficients (D33)mentioning
confidence: 99%
See 1 more Smart Citation
“…The production processes and poling methods for this arrangement have also been previously studied, in particular with respect to the study of the influence of the conductive layers on the piezoelectric properties of the PVDF [9][10][11]. Comprehensive work by Lund et al [10] and Ferreira et al [11] have shown for twolayered filaments that the electroactive phase content is not affected by the conductive inner core.…”
Section: Piezoelectric Polymers and Filamentsmentioning
confidence: 99%
“…More importantly, the piezoelectric fiber retained its performance even after three days' cyclic bend-release tests. Compared to other piezoelectric fibers [20][21][22][23]28 , the fibers presented in this work feature a swiss roll structure of the piezoelectric layer, which considerably increases the active surface area and reduces the layer thickness, this resulting in considerably higher voltages and currents (and consequently electric powers) that can be generated by such fibers. Large-area piezoelectric textiles could be fabricated by incorporating the drawn fibers into woven fabrics, thanks to their excellent mechanical properties (as they are made only of plastics), and the use of low-cost, high volume fabrication techniques (fiber drawing).…”
mentioning
confidence: 99%